Echocardiography of primitive ventricle. Issue 8 (August 1977) - Mortera, C; Hunter, S; Terry, G; Tynan, M
Abstract : The angiocardiographic, echocardiographic, and, where available, the necropsy findings were correlated in 32 cases of primitive ventricle. Single probe echocardiography was shown to be a reliable and accurate technique for diagnosis of primitive ventricle; the ventricular and atrioventricular valve appearances were characteristic, and the outlet chamber was usually recognised when present, though it was not possible to say whether it was rigt or left sided. Abnormalities of the atrioventricular valves were more accurately shown by echocardiography than by angiocardiography though the two techniques were shown to be complementary in the overall diagnostic process.